2019
DOI: 10.1111/ina.12589
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pulmonary ventilation rate and breathing cycle period on the risk of cross‐infection

Abstract: This study examined the characteristics of the exhaled airflow pattern and breathing cycle period of human subjects and evaluated the influence of pulmonary ventilation rate and breathing cycle period on the risk of cross‐infection. Measurements with five human subjects and a breathing thermal manikin were performed, and the peak exhaled airflow velocity from the mouth and the breathing cycle period were measured. Experiments on cross‐infection between two breathing thermal manikins were then conducted in a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 45 publications
(124 reference statements)
0
26
0
Order By: Relevance
“…This airflow interaction in the human body microenvironment is complex ( Melikov, 2015 ) and has a major impact on short-distance exposure ( Melikov and Ai, 2020 ). Research has shown that short-distance exposure in ventilated rooms occurs when the distance between the exposed occupant and the infected person is less than 1–1.5 m ( Ai and Melikov, 2018 , Ai et al, 2019 ). Long-distance exposure occurs at distances between occupants of more than 1–1.5 m when the pollution is more or less mixed with the air in the occupied zone.…”
Section: The Process Of Ventilation and Exposurementioning
confidence: 99%
“…This airflow interaction in the human body microenvironment is complex ( Melikov, 2015 ) and has a major impact on short-distance exposure ( Melikov and Ai, 2020 ). Research has shown that short-distance exposure in ventilated rooms occurs when the distance between the exposed occupant and the infected person is less than 1–1.5 m ( Ai and Melikov, 2018 , Ai et al, 2019 ). Long-distance exposure occurs at distances between occupants of more than 1–1.5 m when the pollution is more or less mixed with the air in the occupied zone.…”
Section: The Process Of Ventilation and Exposurementioning
confidence: 99%
“…This has been confirmed by experiments and modelling studies of aerosol dynamics. 17 , [28] , [29] , [30] , [31] , [32] , [33] …”
Section: Introductionmentioning
confidence: 99%
“…However, to date, most of the thermo-fluid dynamic analyses performed on this very complex subject are limited to non-pathogen carrying droplet emission and/or simulate simplified conditions (e.g. constant emission, steady-state analyses) ( Ai et al, 2019 ; Ai and Melikov, 2018 ).…”
Section: Introductionmentioning
confidence: 99%